The potential neuroprotective roles of olive leaf extract in an epilepsy rat model induced by kainic acid - Safoura Khamse; Saeed Mohammadian Haftcheshmeh; Seyed Shahabeddin Sadr; Mehrdad Roghani; Mohammad Kamalinejad; Parvane Mohseni Moghaddam; Ravieh Golchoobian; Fatemeh Ebrahimi (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Epilepsy is recognized as a chronic neurologic disease. Increasing evidence has addressed the antioxidant and anti-inflammatory roles of olive leaf extract (OLE) in neurodegenerative diseases. So, the current study aimed to investigate the neuroprotective roles of OLE in epilepsy. Experimental approach: Forty rats were divided into 4 groups including a control group, sham group, kainic acid (KA) group, and KA + OLE group. KA (4 μg/rat) was injected intrahippocampal, and OLE (300 mg/kg) was orally administrated for 4 weeks. Animals were sacrificed, and their hippocampi were isolated. KA- induced seizure activity was recorded. Oxidative stress index was assessed by measuring its indicators including malondialdehyde (MDA), nitrite, nitrate, and glutathione (GSH) as well as the catalase (CAT) activity. The supernatant concentration of tumor necrosis factor-α (TNF-α) and the apoptosis rate in neurons were measured. Findings/Results: Treatment with OLE significantly reduced the seizure score. OLE decreased oxidative stress index by reducing the concentration of MDA, nitrite, and nitrate as well as increasing the level of GSH. OLE had a significant anti-apoptotic effect on neurons. However, CAT activity and the level of TNF-α were not affected. Conclusion and implications: Our findings indicated neuroprotective properties of OLE, which is mainly mediated by its antioxidant and anti-apoptotic effects, therefore, could be considered as a valuable therapeutic supplement for epilepsy.